Marketing or Transparency? A Study into Misleading Labelling: With Food Experts, Consumers and the Food Sector - Annet J. C. Roodenburg; Nadja Hanssen; Gerlinde van Santen (Proceedings)
Background and objectives: Despite the current food labelling legislation, there is room for marketing departments in the food industry to seduce consumers with misleading labelling, for example by using pictures of fresh fruits or vegetables that are only present in tiny amounts in the product, or by using terms such as ‘no added sugar’, ‘natural’, ‘healthy’ or ‘fresh’, misleading portion sizes and fun characters for kids. Consumers need help in making the actual healthy choice. So, what needs to be done and by whom? Methods: Several studies were carried out: Semi-structured interviews (n = 7) with food experts on roles and responsibilities of different parties and possible solutions. Based on an inventory of misleading food labels, a categorization was made together with the help of food experts. The eight defined categories were evaluated in quantitative (n = 1117) and qualitative (n = 26) consumer studies. A selection of legislative measures against misleading labelling that are already available in other countries were evaluated in 12 semi-structured interviews with representatives from the food industry. Results and Discussion: Consumers indicated that the top three categories of most misleading labelling were (1) the suggestion of product qualities that are not present or are only present in tiny amounts; (2) blurring of unhealthy ingredients; and (3) incorrect use of nutrition claims. Misleading labelling was mostly found on cookies, bars and non-alcoholic drinks. In general, the representatives of the food industry agreed on the need for legislation to prevent blurring of unhealthy nutrients and incorrect use of nutrition claims. Suggesting product qualities that are not present or are present in tiny amounts was of a lower priority according to the interviewees. It was indicated that there is a tension between the marketing and quality roles within a food company. With respect to roles and responsibilities, there was an agreement that the food producers were responsible for what is on their packages, the government is responsible for the legislation and the consumers are responsible for their own food choices. However, everyone doubts whether the consumers understand enough to be able make healthier choices.